Unravelling structural ambiguities in lithium- and manganese-rich transition metal oxides - Shukla, Alpesh Khushalchand; Ramasse, Quentin M.; Ophus, Colin; Duncan, Hugues; Hage, Fredrik; Chen, Guoying (Nature communications, 2015)
Although Li- and Mn-rich transition metal oxides have been extensively studied as high-capacity cathode materials for Li-ion batteries, the crystal structure of these materials in their pristine state is not yet fully understood. Here we apply complementary electron microscopy and spectroscopy techniques at multi-length scale on well-formed Li 1.2 (Ni 0.13 Mn 0.54 Co 0.13 )O 2 crystals with two different morphologies as well as two commercially available materials with similar compositions, and unambiguously describe the structural make-up of these samples. Systematically observing the entire primary particles along multiple zone axes reveals that they are consistently made up of a single phase, save for rare localized defects and a thin surface layer on certain crystallographic facets. More specifically, we show the bulk of the oxides can be described as an aperiodic crystal consisting of randomly stacked domains that correspond to three variants of monoclinic structure, while the surface is composed of a Co- and/or Ni-rich spinel with antisite defects. Lithium and manganese-rich transition metal oxides are a class of promising battery electrodes but their structures are a subject of a controversial debate. Here, the authors use a variety of materials characterization tools to unravel the structural ambiguities in these materials.